New Hybrid Hole Extraction Layer of Perovskite Solar Cells with a Planar p-i-n Geometry - Park, Ik Jae; Park, Min Ah; Kim, Dong Hoe; Park, Gyeong Do; Kim, Byeong Jo; Son, Hae Jung; Ko, Min Jae; Lee, Doh-Kwon; Park, Taiho; Shin, Hyunjung; Park, Nam-Gyu; Jung, Hyun Suk; et al. (American Chemical Society, 2015)
We report a highly efficient p-i-n type planar perovskite solar cell with a hybrid PEDOT/NiOx hole-extraction layer. It has been found that the perovskite solar cell with a NiOx thin film as a hole-extraction layer generally exhibits lower fill factor compared to the conventionally used PEDOT:PSS thin film, whereas it shows higher photocurrent and photovoltage. The fill factor of the NiOx-based perovskite solar cell can be significantly improved by treating the NiOx surface with a dilute PEDOT solution. The photoluminescence quenching study and impedance spectroscopic (IS) analysis have revealed that the hole injection at the perovskite/NiOx interface is significantly facilitated with the PEDOT treatment, which should lead to the increased fill factor. As a result, the p-i-n type planar perovskite solar cell with the new hybrid hole-extraction layer exhibits a high conversion efficiency of 15.1% without the hysteresis effect.
Keywords: HIGH-PERFORMANCE; NICKEL-OXIDE; THIN-FILM; CH3NH3PBI3; EFFICIENCY; TRIHALIDE; HYSTERESIS